How Topology Changes Under Disruptive Conditions Affect Transportation System Resilience A Case Study of Colombo - LDCHN, Kalpana; KATO, Teppei; SANO, Kazushi (Journal of the Eastern Asia Society for Transportation Studies, 2024)
The transportation system is a critical infrastructure with profound impacts on the economy and social well-being. Therefore, understanding and enhancing transportation system resilience in the face of disruptions is of utmost importance. This study presents a framework that utilizes critical-link attacks to disrupt transportation network segments, evaluating their resilience. By utilizing network topological parameters as proxies, the framework holistically captures the network's resilience, considering all potential individual road segment disruptions. In contrast to conventional studies focusing on pre-hazard occurrences, this framework incorporates worst-case scenarios, encompassing all potential individual disruptions. Statistical and spatial analysis techniques are employed to assess transportation network resilience in both macro and micro events, employing topological parameters to evaluate network changes under varying levels of disruption. The results demonstrate the effectiveness of topological parameters in capturing transportation system resilience, enabling the identification of critical road segments from structural and network perspectives. These findings contribute to evaluating network performance and ensuring optimal transportation serviceability.